Anti‐adhesive effects of a newly developed two‐layered gelatin sheet in dogs. Issue 8 (29th May 2017) - Torii, Hiroko; Takagi, Toshitaka; Urabe, Mamoru; Tsujimoto, Hiroyuki; Ozamoto, Yuki; Miyamoto, Hiroe; Ikada, Yoshihito; Hagiwara, Akeo
Abstract: Aim: Adhesion after pelvic surgery causes infertility, ectopic pregnancy, and ileus or abdominal pain. The materials currently available for clinical use are insufficient. The purpose of this study was to develop an anti‐adhesive material that overcomes the limitations of conventional anti‐adhesive agents. Methods: The adhesion prevention effects of three methods – a two‐layered sheet composed of gelatin film and gelatin sponge, Seprafilm and INTERCEED – were evaluated in 37 dogs. Anti‐adhesive effects were investigated macroscopically and microscopically in a cauterized uterus adhesion model. Cell growth on the materials in vitro using human peritoneal mesothelial cells, fibroblasts and uterine smooth muscle cells were also evaluated. Results: The two‐layered gelatin sheet had significantly superior anti‐adhesive effects compared to the conventional materials (Seprafilm and INTERCEED). A single‐cell layer of mature mesothelium formed three weeks after surgery in the gelatin group. Peritoneum regeneration in the Seprafilm and INTERCEED groups was delayed and incomplete in the early phase. Little inflammation around the materials occurred and cell growth was significantly proliferated with the gelatin sheet. Conclusion: The anti‐adhesive effects of a two‐layered gelatin sheet were superior to conventional agents in a cauterized canine uterus model, demonstrating early regeneration of the peritoneum, little inflammation and material endurance. The newly developed two‐layered gelatin sheet is a useful option as an anti‐adhesive agent for deeply injured and hemorrhagic sites.